Enhancement of Yellow Light Extraction Efficiency of Y 3Al 5O 12:Ce 3+ Ceramic Converters Using a 2-D TiO 2 Hexagonal-Lattice Nanocylinder Photonic Crystal Layer - Haiding Sun; Alan Piquette; Madis Raukas; Theodore D. Moustakas (IEEE Photonics Journal)
The effects of 2-D hexagonal-lattice TiO 2 photonic crystal layers on the directional light extraction efficiency of low-scattering (Y 1-xCe x) 3Al 5O 12 (YAG:Ce 3+) ceramic converters have been investigated. The hexagonal-lattice TiO 2 patterns were fabricated by an electron beam lithography process. The optimized yellow directional light extraction enhancement by a factor of 4.4 is achieved with a 2-D photonic crystal layer having a diameter of 430 nm, a lattice constant of 590 nm, and a height of 350 nm. A 3-D finite-difference time-domain model has also been developed to study the geometric parameters of the photonic crystal layer, yielding results that are consistent with our measured data.